2011
DOI: 10.1177/1477370810393156
|View full text |Cite
|
Sign up to set email alerts
|

Worlds tied together? Online and non-domestic routine activities and their impact on digital and traditional threat victimization

Abstract: The article compares risk factors between threat victimization by digital and traditional modes (e.g. email or chat room versus letter or face-to-face). Until now, empirical tests of routine activity theory have applied a segregated approach in such cases, linking computer activities to cybercrime victimization and outdoor activities to traditional victimization. However, an integrated approach suggests that social interactions between people in the physical and digital world are connected. Thus, exposure to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
63
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 23 publications
2
63
0
1
Order By: Relevance
“…The impact of new technologies and inadequate security on the likelihood of insider victimization can be estimated using Routine Activities Theory (Cohen and Felson 1979). Several empirical applications point to the significant effect that frequent routine activity and the lack of capable guardians have on opening-up opportunities for cybercrime (Holt and Bossler 2008;Van Wilsem 2011;Williams 2016). This paper extends this work to explore whether corporate insider cybercrime victimization is a function of risky routine activities conducted in organizations that lack capable guardianship.…”
mentioning
confidence: 87%
See 2 more Smart Citations
“…The impact of new technologies and inadequate security on the likelihood of insider victimization can be estimated using Routine Activities Theory (Cohen and Felson 1979). Several empirical applications point to the significant effect that frequent routine activity and the lack of capable guardians have on opening-up opportunities for cybercrime (Holt and Bossler 2008;Van Wilsem 2011;Williams 2016). This paper extends this work to explore whether corporate insider cybercrime victimization is a function of risky routine activities conducted in organizations that lack capable guardianship.…”
mentioning
confidence: 87%
“…However, there are a number of studies based on the domestic population. Studies of cyber-harassment and computer virus infection have shown proximity to motivated offenders and varied and intense online routine activity were predictive of victimization (Holt and Bossler 2008;Van Wilsem 2011). Perhaps most pertinent to insider cyber victimization, studies of online identity theft among domestic victims have produced some encouraging results.…”
Section: Insider Cybercrime: a Routine Activities Theory Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Computers and the internet have dynamically changed the possibilities for experiencing crime [23]. Now not only can computers be targets for crime, but crimes can now be conducted on the internet as well [23].…”
Section: Discussionmentioning
confidence: 99%
“…Now not only can computers be targets for crime, but crimes can now be conducted on the internet as well [23]. VPT and cybercrime represent the most undesirable aspects of VWEs, as with the internet in general.…”
Section: Discussionmentioning
confidence: 99%